An Irish country practice [large type] - Taylor, Patrick, 1941- (Taylor, Patrick, 1941- Irish country novel, 2017)
"Once, not too long ago, there was just a single Irish country doctor tending to the lively little village of Ballybucklebo: Doctor Fingal Flahertie O'Reilly. Now his thriving practice is growing by leaps and bounds. Not only has O'Reilly taken a new trainee under his wing, Doctor Connor Nelson, he's also added a spirited Labrador puppy to his ever-expanding household at Number One Main Street. Meanwhile, his trusted partner, young Doctor Barry Laverty, finds himself wondering if he's truly ready to settle down and start a family with his lovely fiancée, Sue. As the doctors cope with domestic and professional challenges, they also look after their patients and their ailments... All is not sickness and worry, however. There's plenty of joy and merriment to be found as well, from a visiting circus to racing to sailing... and maybe even a happy ending or two."--Book jacket.